KERAGAAN PERTUMBUHAN HIBRIDISASI EMPAT STRAIN IKAN MAS - MH Fariduddin Ath-thar; Vitas Atmadi Prakoso; Rudhy Gustiano (Research Center for Biology-Indonesian Institute of Sciences, 2011)
One way to support the increase of aquaculture production is to produce superior strains of growth. Carp as one of the potential for these commodities only rely on local strains which have had a decline in quality. For that, the effort to generate superior growth of carp need to be done. One way to do that is by hybridization. We carried out reciprocal crosses of 4 strains of carp Rajadanu, Subang, Majalaya and Kuningan to obtain 16 new strain candidates. Furthermore, growth test was conducted to find out the best candidate of the absolute and specific growth parameters. From these results, it was concluded that the absolute growth in length, weight, and the highest biomass obtained by crosses of SB x RD, the highest length and weight Specific Growth Rate obtained by crosses of RD x MJ. For the highest degree of survival is at the intersection of KN x SB, whereas the highest survival rate in the use of female parent KN. In the dominant male of female survival is the parent SB. The biggest positive heterosis character length growth values obtained by crosses of SB x RD. For the highest weight growth heterosis values obtained by crosses of SB x MJ. On the character of hatching, the highest positive heterosis values obtained by crosses of SB x MJ. The degree of survival of the highest heterosis values obtained by crosses of KN x MJ. On the character of the highest positive heterosis values of biomass obtained by crosses of SB x MJ. As for the character length SGR highest positive heterosis values obtained by crossing two directions of RD and SB. And for the character weight Specific Growth Rate, the highest positive heterosis values obtained by crossing two ways KN and MJ.